Ways of interpretation the author’s conception of narrative Gradov town written by A. Platonov - Гордович, Кира (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The narrative Gradov town written by A. Platonov attracted attention of many researchers in Soviet and Post Soviet periods. The most interesting approaches to interpretation are revealed in this work: widening of “bureaucracy” and “red tape” meaning; a problem of revolutionary tasks substituted by bureaucrats’ victories; a way of traditions’ using. Some unsuccessful attempts of philological analysis of the narrative were mentioned.